An abandoned railway reborn as a short distance transportation mode. Case study : Port Dickson, Negeri Sembilan - Saifurizal, Nurul Izzatie (2018)
Today, abandoned and disused railway is a real-life issue for many country communities, to which they unsurprisingly react. One of the terms of the inquiry was to review options for better targeting of funding and delivery of public transport services to meet the needs of nonmetropolitan communities, including rural community and health transport needs. The relationship between the railway station and the city has always been characterized by episodes of conflict. The infrastructure nodes represent the complex society and devoted to the movement, but also a chance to resolve old tensions that are due to a shared space, and to avoid creating poor urban areas between the railway infrastructure and the urban environments. Some projects, by redesigning the pre-existing station, have given value to the empty spaces with new elements or with the use of existing elements. The design goal for this project is to regenerate and preserve the Port Dickson’s historical railway track into an accessible, memorable and lively linear railway park that act as a catalyst to development and local community involvement. Design objectives are established with the theme towards nature, learning and healthy lifestyle by optimizing pedestrian, linear spaces and its function as well as connectivity between existing hotspot areas. To accomplish the goal of this project, there are three objectives includes To reveal and strengthen the traces of history and cultural heritage of Port Dickson Old Town Business; To preserve and promote the historical value of the abandoned railway track of Port Dickson; and To enhance the public spaces of Port Dickson. At the same time, they have produced vital large parts of the city. Indirectly, in order to preserve the strong image of an abandoned railway, the transformation process involved which to make it as a small part of the greenway system in Port Dickson District and even in Negeri Sembilan in line with what the design proposal tried to achieve in the future.